Adapting interventions to new contexts—the ADAPT guidance. (3rd August 2021) - Moore, Graham; Campbell, Mhairi; Copeland, Lauren; Craig, Peter; Movsisyan, Ani; Hoddinott, Pat; Littlecott, Hannah; O'Cathain, Alicia; Pfadenhauer, Lisa; Rehfuess, Eva; Segrott, Jeremy; Hawe, Penelope; et al.
Abstract : Implementing interventions with a previous evidence base in new contexts might be more efficient than developing new interventions for each context. Although some interventions transfer well, effectiveness and implementation often depend on the context. Achieving a good fit between intervention and context then requires careful and systematic adaptation. This paper presents new evidence and consensus informed guidance for adapting and transferring interventions to new contexts.